Weekend screen use of parents and children associates with child language skills - Tulviste, Tiia; Tulviste, Jaan (Frontiers in Developmental Psychology, 2024)
The study examined the relationship between screen time and types of screen activities engaged in by children, mothers, and fathers on weekends, and its association with mother-reported vocabulary and grammatical skills of children aged 2;5 to 4;0. Mothers reported the language skills of 421 children (M age = 38.18 months; SD = 5.73) by the Estonian CDI-III, and the screen use of children, mothers, and fathers by the Screen Time Inventory. The results showed that higher total screen time of children was linked to poorer vocabulary and grammatical skills. None of the screen-based activities that children, mothers, and fathers engaged in, including co-viewing of screens and socializing time, were found to positively relate to language skills. Playing video games was negatively associated with children's language skills, regardless of whether it was the child, mother, or father gaming. By applying Latent Class Analysis (LCA) to analyze the screen time of children, mothers, and fathers, we identified 3 distinct family screen use profiles (low, moderate, and high users), and these profiles differed by parental education, screen-based activities, and children's language skills. The findings underscore the significance of family-based interventions when addressing screen time within the context of child language development.